Her deadly secrets : a novel - Griffin, Laura, 1973- (Tracers series, 2019)
A young private investigator finds out the price of keeping deadly secrets when a vicious killer sets his sights on her in this pulse-pounding thriller from the USA TODAY and New York Times bestselling author of the Tracers series.